2009
DOI: 10.13102/scb8012
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Gaibulus schubarti Roewer 1973 (Opiliones: Stygnidae) in treefall gaps of Atlantic forest

Abstract: Objetivou-se ampliar o conhecimento da opiliofauna nordestina, comparar variáveis ambientais e abundância de Gaibulus schubarti entre sítios de clareira natural e mata adjacente em um fragmento de Mata Atlântica urbana, além de verificar se cobertura e profundidade de serrapilheira influenciam na abundância destes artrópodes. No Parque Metropolitano de Pituaçu (425 ha), fragmento de Mata atlântica, foram selecionados 12 pontos (6 clareira e 6 Mata). Durante 12 meses, foram coletados mensalmente nos 12 sítios, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Second, genus identification for many individuals is still difficult (Cardoso et al, 2004), especially for non‐specialists in the group. Several harvestmen diversity studies, mainly the ones prior to most recent reviews, present individuals that are not identified at the genus level, for example, in the subfamilies Gonyleptinae, Pachylinae and Tricommatinae (Andrade et al, 2009; Bragagnolo & Pinto‐da‐Rocha, 2003; Bragagnolo et al, 2007; Pinto‐da‐Rocha et al, 2005; Resende et al, 2012a, 2012b). The same was observed in the present study: subfamilies such as Pachylinae, Heteropachylinae, Tricommatinae and Escadabiidae presented individuals whose identification at the genus level was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Second, genus identification for many individuals is still difficult (Cardoso et al, 2004), especially for non‐specialists in the group. Several harvestmen diversity studies, mainly the ones prior to most recent reviews, present individuals that are not identified at the genus level, for example, in the subfamilies Gonyleptinae, Pachylinae and Tricommatinae (Andrade et al, 2009; Bragagnolo & Pinto‐da‐Rocha, 2003; Bragagnolo et al, 2007; Pinto‐da‐Rocha et al, 2005; Resende et al, 2012a, 2012b). The same was observed in the present study: subfamilies such as Pachylinae, Heteropachylinae, Tricommatinae and Escadabiidae presented individuals whose identification at the genus level was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…This group of organisms is ideal to understand the consequences of habitat modification on biodiversity. Among invertebrates, harvestmen have recently gained attention in conservation studies (e.g., Bragagnolo et al 2007; Merino‐Sáinz & Anadón 2018; Tourinho et al 2020) due to their low dispersion capacity (Pinto‐da‐Rocha et al 2005) and responses to habitat changes and environmental gradients, such as temperature and humidity (e.g., Andrade et al 2009; Nogueira et al 2019; Piñeiro‐Passos et al 2016). It is important to note that environmental variables can easily be linked to the vegetation structure (Merino‐Sáinz & Anadón 2015; Proud et al 2011; Stasiov et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, approximately 15% of the species in this group have been described from Brazil (Kury et al 2020). Although there is a high level of endemism in Neotropical rainforests (Pinto‐da‐Rocha et al 2005), ecological studies on harvestmen are scarce in these regions, especially in one of the most representative and threatened ecosystems, the Atlantic Forest (Andrade et al 2009; Bragagnolo et al 2007; Lira & DeSouza 2016; Nogueira et al 2019; Piñeiro‐Passos et al 2016).…”
Section: Introductionmentioning
confidence: 99%